2001
DOI: 10.1034/j.1600-0714.2001.300301.x
|View full text |Cite
|
Sign up to set email alerts
|

Type II nitric oxide synthase (NOS2) expression correlates with lymph node status in oral squamous cell carcinoma

Abstract: In tumour biology, nitric oxide (NO) has a complex array of concentration-dependent actions, including both inhibitory and promoting effects. It is thought that the levels of NO found in many human cancers lead to enhanced angiogenesis and tumour dissemination. In the current study, we assessed the immunohistochemical expression of the enzyme type II nitric oxide synthase (NOS2) in 41 cases of oral squamous cell carcinoma and correlated the findings with lymph node status. A significant relationship was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 26 publications
6
31
0
2
Order By: Relevance
“…Although it is now becoming increasingly evident that NO itself probably promotes growth of human tumours by facilitating both angiogenesis and dissemination 8,11 , little is known about the effect of NOS-released NO on tumour cells themselves. In the present study, it was found for the first time that L-NAME, an active NOS inhibitor, could partly inhibit TSCCa cells both concentration and…”
Section: Discussionmentioning
confidence: 99%
“…Although it is now becoming increasingly evident that NO itself probably promotes growth of human tumours by facilitating both angiogenesis and dissemination 8,11 , little is known about the effect of NOS-released NO on tumour cells themselves. In the present study, it was found for the first time that L-NAME, an active NOS inhibitor, could partly inhibit TSCCa cells both concentration and…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry for inducible NOS (iNOS), endothelial NOS (eNOS), and HIF-1a proteins was carried out on 29 formalin-fixed specimens of human oral squamous cell carcinoma and 10 samples of normal oral mucosa. Monoclonal antibodies to iNOS, eNOS (BD Biosciences, Oxford, United Kingdom), and HIF-1a (Novus Biologicals, Littleton, CO) were used as previously described (16,17), and samples were developed using an avidin biotin horseradish peroxidase system (DAKO, Glostrup, Denmark). Positive controls were normal kidney for HIF-1a and an oral squamous cell carcinoma known to have high eNOS expression and activity.…”
Section: Methodsmentioning
confidence: 99%
“…In those experiments, however, NO was either added exogenously or generated in an overexpressed cell system. In view of this, we decided to investigate whether endogenous NO is involved in the presence of HIF-1a in human oral squamous cell carcinoma, a malignancy in which both HIF-1a and NO are known to occur (10,16). To do this, we studied the distribution of NO synthase (NOS) and of HIF-1a in samples of human oral carcinoma tissue and in cell lines obtained from human oral squamous cell carcinoma, where we also investigated the effect of free radical production on HIF-1a expression.…”
Section: Introductionmentioning
confidence: 99%
“…Correlation between NOS expression and tumor progression, including lymph node metastases, has been reported in human oral squamous cell carcinoma [9,35], gastric carcinoma [36], and breast cancer [37]. Breast cancer patients testing positive for iNOS were found to have significantly lower 5-year survival rate than patients who tested negative for iNOS [37].…”
Section: Discussionmentioning
confidence: 92%